The performance of heparin modified poly(ε‐caprolactone) small diameter tissue engineering vascular graft in canine—A long‐term pilot experiment in vivo. Issue 12 (7th June 2021) - Ye, Lin; Takagi, Toshitaka; Tu, Chengzhao; Hagiwara, Akeo; Geng, Xue; Feng, Zengguo
Abstract: Long‐term in vivo observation in large animal model is critical for evaluating the potential of small diameter tissue engineering vascular graft (SDTEVG) in clinical application, but is rarely reported. In this study, a SDTEVG is fabricated by the electrospinning of poly(ε‐caprolactone) and subsequent heparin modification. SDTEVG is implanted into canine's abdominal aorta for 511 days in order to investigate its clinical feasibility. An active and robust remodeling process was characterized by a confluent endothelium, macrophage infiltrate, extracellular matrix deposition and remodeling on the explanted graft. The immunohistochemical and immunofluorescence analysis further exhibit the regeneration of endothelium and smooth muscle layer on tunica intima and tunica media, respectively. Thus, long‐term follow‐up reveals viable neovessel formation beyond graft degradation. Furthermore, the von Kossa staining exhibits no occurrence of calcification. However, although no TEVG failure or rupture happens during the follow‐up, the aneurysm is found by both Doppler ultrasonic and gross observation. Consequently, as‐prepared TEVG shows promising potential in vascular tissue engineering if it can be appropriately strengthened to prevent the occurrence of aneurysm. Abstract :